Cdc14-regulated midzone assembly controls anaphase B - Khmelinskii, Anton (The Rockefeller University Press, 2007)
Spindle elongation in anaphase of mitosis is a cell cycle–regulated process that requires coordination between polymerization, cross-linking, and sliding of microtubules (MTs). Proteins that assemble at the spindle midzone may be important for this process. In this study, we show that Ase1 and the separase–Slk19 complex drive midzone assembly in yeast. Whereas the conserved MT-bundling protein Ase1 establishes a midzone, separase–Slk19 is required to focus and center midzone components. An important step leading to spindle midzone assembly is the dephosphorylation of Ase1 by the protein phosphatase Cdc14 at the beginning of anaphase. Failure to dephosphorylate Ase1 delocalizes midzone proteins and delays the second, slower phase of anaphase B. In contrast, in cells expressing nonphosphorylated Ase1, anaphase spindle extension is faster, and spindles frequently break. Cdc14 also controls the separase–Slk19 complex indirectly via the Aurora B kinase. Thus, Cdc14 regulates spindle midzone assembly and function directly through Ase1 and indirectly via the separase–Slk19 complex.